Information needs and information-seeking behavior of university students in Bandung Raya - Putri, Dea Ananda; Prijana, Prijana; Chigbundu, Michael Chinweike (Jurnal Kajian Informasi dan Perpustakaan, 2024)
This study addresses the specific information needs and information-seeking behavior of university students in Bandung Raya, which have yet to be widely explored in the current academic literature. Furthermore, there needs to be more information on how university students navigate information sources in searching for the information they need and the types of information they usually seek. Therefore, the researcher directed this study to determine the information needs and information-seeking patterns of students with a focus on university students in Bandung Raya. The study adopted a quantitative research design. A total of 602 students were the research sample. The online questionnaire was randomly administered to sample students. The authors found that the cognitive needs of university students in Bandung Raya were correlated with the initiation stage of the information seeking initiation stage. The authors also discovered that the cognitive needs of Bandung Raya students were correlated to the exploration stage of information search. Besides, the authors found that the formulation stage of information seeking was related to Bandung Raya students' cognitive needs. However, the research findings revealed that the Bandung Raya students' affective needs were more related to the selection stage, collection stage, and presentation stage of information-seeking behavior. The results of this study indicated the vital role of students’ affective and cognitive needs in shaping the way students sought the information they needed and why authorities should pay more attention to students' cognitive and affective needs for better academic performance.